Percepção de profissionais da estratégia Saúde da Família sobre o prontuário eletrônico do cidadão - Oliveira, Luciane Silva (2024)
The medical record is a document that gathers information from patients registered by health professinals, such as specific data from the anamnesis, clinical examination and therapeutic prescriptions. To optimize this record, the Electronic Citizen Record was implemented, which contributes to comprehensive care, promoting agility in clinical diagnosis, conduct and treatment, optimizing the patient's and health professionals' time. Objective: Evaluate the usability of the PEC by family health strategy professionals. Method: Cross-sectional and quantitative study, carried out with 260 health professionals from Primary Health Care in Sobral. Professionals who had been using the PEC for at least three months were included. Professionals who were on leave during the data collection period, due to vacation, health or maternity leave, were excluded; those who did not express interest in participating in the study after three attempts and professionals from other municipalities. For data collection, the instrument adapted to evaluate the Electronic Citizen Record of the e-SUS Strategy was used, with 27 questions. The research data was stored in the Microsoft Excel® program and analyzed in EPI INFOTM. The research received ethical approval (no. 6,256,282/2023). Results: 260 health professionals participated, most of them women (80.77%), with an average age of 34.67 (±9.6) years. It was identified that 56.54% are nurses, doctors, NASF professionals and other higher education professionals, 54.13% have employment in the form of a temporary contract in the Basic Health Unit. In the analysis of satisfaction with the use of the PEC, 64.23% agreed that they were satisfied and 28.85% strongly agreed. Regarding the daily usability of the PEC, 55.77% strongly agreed that the PEC interface is easy to use. It was observed that 89.23% of professionals agree with the ease of using all the tools available in the PEC. Of the 260 professionals, 57.31% agree or strongly agree (31.54%) that they can easily view patient information in the PEC and 84.23% agree that it is possible to obtain or retrieve information from the PEC easily. Furthermore, 93.08% agreed that the PEC provides agility in customer service, with improvements in data recording. It was identified that 90% agree that they are qualified to use the PEC and 75.77% use WhatsApp© groups to clarify doubts regarding the use of the PEC. Regarding the training received to use the PEC offered by the State Department of Health, 54.61% agree that they received it and 45.38% disagree. It was also identified that 58.85% agree and 26.54% strongly agree that the information in the reports generated by the PEC is used for work management. There was no significant association between the investigated sociodemographic and professional variables. A significant association was observed between employment and PEC usability (p=0.000). Conclusion: Based on the study's results, a generally positive receptivity from health professionals towards using PEC is evident. The majority demonstrated satisfaction with the usability, facilitating access to patient information and providing agility in care. Despite differences regarding the provision of training by the State Department of Health, the results suggest that the PEC is an effective tool for managing health work, highlighting its importance in optimizing the services provided.